Suxiao Jiuxin Pill Induces Potent Relaxation and Inhibition on Contraction in Human Artery and the Mechanism. (7th April 2014) - Bai, Xiao-Yan; Zhang, Ping; Yang, Qin; Liu, Xiao-Cheng; Wang, Jun; Tong, Yong-Ling; Xiong, Song-Jin; Liu, Li-Hua; Wang, Lei; He, Guo-Wei
Abstract : Suxiao Jiuxin Pill, a compound Chinese traditional medicine with main components of tetramethylpyrazine and borneol, is widely used for antiangina treatment in China but its pharmacological effect on human blood vessels is unknown. We investigated the effect and possible mechanism of SJP in the human internal mammary artery (IMA, n = 78 ) taken from patients undergoing coronary surgery. SJP caused full relaxation in KCl- (99.4 ± 10.5 %, n = 6 ) and U46619- (99.9 ± 5.6 %, n = 6 ) contracted IMA. Pretreatment of IMA with plasma concentrations of SJP (1 mg/mL), calculated from the plasma concentration of its major component borneol, significantly depressed the maximal contraction to KCl (from 35.8 ± 6.0 mN to 12.6 ± 5.6 mN, P = 0.03 ) and U46619 (from 19.4 ± 2.9 mN to 5.7 ± 2.4 mN, P = 0.007 ) while SJP at 10 mg/mL abolished the subsequent contraction. Endothelium denudation and inhibition of eNOS significantly altered the SJP-induced relaxation without changes of eNOS expression. We conclude that SJP has a potent inhibitory effect on the vasoconstriction mediated by a variety of vasoconstrictors in human arteries. The vasorelaxation involves both endothelium-dependent and -independent mechanisms. Thus, the effect of SJP on human arteries demonstrated in this study may prove to be particularly important in vasorelaxing therapy in cardiovascular disease.